Plastic Surgery for the Oncological Patient - Adrien Daigeler (Frontiers Research Topics, 2016)
The develoment of plastic surgery techniques allows for preserving and reconstruction of function after resection of malignant tumors. From split thickness skin grafts to pedicled and free tissue transfer multiple techniques are at hand to restore body integrity. Sufficient soft tissue coverage allows for adjuvant radiation therapy or can cure its sequelae. Nerve, tendon and muscle transfers are used to regain motor function of the extremities. Even large bony defects can be treated by microsurgically transferring fibula, pelvic and femoral bone. In case main vessels need to be resected reconstruction is possible with autologous and artificial grafts. By means of plastic surgery thoracic and abdominal defects can be covered so that foremost unresectable tumors become curable. Unfortunately the knowledge of these techniques is not very popular with oncologic surgeons. Therefore we suggest as a clinical topic the role of reconstructive surgery in the multimodal treatment of oncologic patients. The focus will be on different areas of the body, therefore articels for reconstructional procedures at the head, the extremities, the trunk, the thoracic wall, the breast, and the foot will be invited. Another focus will be the role of reconstructive procedures in the multimodal treatment concept consisting of radiation and chemotherapy as well. By knowing and applying the opportunities of plastic surgery the quality of live of the oncologic patient can be significantly improved.